An incentive mechanism with privacy protection and quality evaluation in mobile crowd computing. (2019) - Long, Hao; Zhang, Shukui; Zhang, Li; Wang, Jin
In order to achieve good service quality for mobile crowd computing (MCC), incentive mechanism need to attract more users to participate in the task while avoiding leakage of privacy. We proposed an incentive mechanism with privacy protection and quality evaluation (IMPPQE). Combining the advantages of offline and online incentive mechanisms, we design improved two-stage auction to select the winners, while protecting participants 'privacy. Finally, the sensing reports are evaluated by quantitative calculation to ensure the objectivity of evaluation. Extensive simulations show that our proposed method can improve the efficiency and utility of MCC and obtain higher satisfaction rate of data quality.